Lipase Production and Optimization from Bioremediation of Disposed Engine Oil - Mahmood, Mahmood H.; Yang, Zhi; Thanoon, Raid D.; Makky, Essam A.; Mohd Hasbi, Ab. Rahim (JOCPR, 2017)
Engine oil is one of the several refined products of crude oil made up of long- chain saturated hydrocarbon (base oil) additives. There are several ways engine oil can enter the environment, such as leaking oil tanks, cleaning of tanks by merchants, warships carrying engine oil, as well as the activities of auto mechanics. Engine oil is a common industrial waste that has harmful environmental and health effects. This study aims to produce lipase enzyme from disposed engine oil (DEO) using a microbial degradation approach. The hydrocarbon-degrading bacterium, GS-3 was isolated from an oil-contaminated area in Kuantan, the capital city of Pahang, a state in Malaysia. Upon GC-MS analysis, it was revealed that GS-3 was able to produce methyl-3, 4, 5-trimethoxy-2, 6-dinitrobenzoate, an organic acid from the DEO. Besides, GS-3 recorded the highest lipase activity of 0.097 ± 0.007 U/ml/min within the first 24 h of activity, using DEO as the only carbon source. The FTIR data revealed the presence of a new broadband at 3421 cm-1 wavelength attributed to the stretching of the O-H group, though a new band occurred at 3424 cm-1 and 1645 cm-1 wavelength after the bioremediation process. The subsequent optimization of the process parameters for the production of lipase revealed that the bacteria perform optimally when the DEO was used as the sole carbon source at the concentration of 4% (v/v), with pH and temperature values of 7.0 and 30°C, respectively. Urea was the best source of nitrogen within the first 24 h of incubation; the addition of Tween 80, a surfactant, enhanced the production of lipase. In conclusion, lipase enzyme production through a microbial process could be a better way to manage DEO and other oil-related environmental contaminants.